(untitled) (PerCursos, 2024)
Traditionally, the field of Brazilian Social Thought has canonized the interpretations of Brazil The research aims to discuss and analyze the representation of black people in university bodies. The research issue concerns the institutional and structural racism present in academia. To this end, the research adopted a quantitative methodology, as well as a case study regarding the black candidacy in the last election for the rectorship of the Federal University of Rio de Janeiro. In parallel with the literature review, the results obtained focus on the profiling of the technical, teaching and support staff of the aforementioned university. In short, it observed the consequences of identity oppression in the social ascension of subjects expropriated of access to goods and power.